MILLENNIAL WOMEN CODE: A STUDY ON PRIDE AND PREJUDICE FILM (2005) - Darisun, Cantika Putri; Maru, Mister Gidion; Lolowang, Imelda (Journal of English Language and Literature Teaching, 2024)
The problem to be investigated in this study is if the movie Pride & Prejudice has a millennial woman code. This movie is worth talking about because it illustrates the resilience of families and how women may overcome cultural expectations when they wed men. It was evident when Elizabeth made an effort to ignore her parents' concerns, which was especially evident to all parents at the time. Her life was filled with difficulties. She can succeed and achieve happiness using all of her skills. The research design in this study was a descriptive qualitative method, because the data was taken from film scripts as primary data, the researchers also used secondary data taken from relevant books and articles. In this study, researchers used liberal feminism theory from Kartika. Where this focuses on the struggles of women to demand their freedom to choose. From the research it was found that the characteristics of millennial women are upheld freedom, having skills, independent and smart. Based on the research results, it can be concluded that there is a millennial woman code in the film Pride & Prejudice, namely the character Elizabeth Bennet. Elizabeth demanded her freedom and the right to choose. This study is expected to provide benefits for future researchers who are conducting research on literature that focuses on feminism or the Pride & Prejudice film.